Radiology of the Stomach and Duodenum - Freeman, Alan H.; Sala, E. (Diagnostic Imaging, 2008)
A number of imaging techniques, many of them complementary, are used in the investigation and treatment of disorders of the stomach and duodenum. Optimal patient treatment requires a thorough knowledge of the application of these techniques, as well as a sound understanding of pathology of the stomach and its presenting symptomatology. This well-illustrated book covers the various investigative methods in detail, discussing their advantages and disadvantages and explaining their role in specific settings. It will be of great value to both trainee and experienced radiologists, and should assist in promoting effective and judicious patient management.